Familial aggregation of Parkinson's disease in the Faroe Islands. Issue 4 (20th January 2015) - Petersen, Maria Skaalum; Bech, Sara; Nosova, Ekaterina; Aasly, Jan; Farrer, Matthew J.
Abstract The Faroe Islands are a geographic population isolated in the North Atlantic with a high prevalence of Parkinson's disease (PD). Although environmental risk factors are well described, the familial aggregation of PD on the Islands has yet to be explored. Complete ascertainment of all patients with PD was performed, including 217 cases and 251 control subjects. All patients were neurologically assessed and diagnosed using UK Brain Bank criteria and Hohn and Yahr staging. Comprehensive genealogical and detailed cartographic analyses were performed. Relative risk and risk ratios were calculated with respect to the general population. Patients with PD in the Faroes have a higher age at symptom onset and diagnosis than for neighboring countries. Clinically, patients are similar; however, they are more likely to have affected relatives than randomly selected control subjects, matched by sex and age. Disease is most prevalent within two geographic regions. Overall, the relative risk for PD was 2.3 (95% confidence interval [CI], 1.2‐4.3; P = 0.008) for siblings and 1.4 (95% CI, 1.01‐1.99, P = 0.04) for first cousins. The etiology and excess prevalence of PD on the Faroes is complicated. Regional and familial clustering, and subsequent segregation analysis, suggests the disease best fits a genetic etiology with limited support for an environmental contribution. Pedigree‐based analysis of PD on the Faroe Islands which has few founders and a relatively homogeneous background may elaborate on these possibilities and their joint contribution. © 2015 International Parkinson and Movement Disorder Society